Exergy analysis of microchannel heat exchangers - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2020)
This study investigates the exergetic efficiencies of four plain microchannel heat exchangers under single-phase and two-phase flow conditions using de-ionised water as the working fluid. The friction factor and heat transfer coefficient data of microchannels are obtained using experimental studies from the literature. The exergetic efficiencies of microchannels are compared to reveal the effect of different geometrical parameters. The results showed that the microchannel aspect ratio is an insignificant parameter on the exergetic efficiency for single-phase flow conditions. However, the exergetic efficiency increased around 90% with the decreasing of the microchannel aspect ratio in two-phase tests. On the other hand, the microchannel heat exchanger having shorter heated length exhibited about 10% and 90% improved exergetic efficiency both in single-phase and two-phase regimes respectively. Moreover, the thermo-economic analysis has been performed in two-phase conditions to propose design guidelines for microchannel heat exchangers from the exergy and thermo-economic performance perspectives.
Keywords: microchannel heat exchanger; exergy analysis; single-phase flow; two-phase flow; thermo-economic analysis; SINGLE-PHASE; FLUID-FLOW; SINKS